Social responsibility of students of medicine: experience in a scientific society of Peruvian students - Chalco Huamán, Joel (2016)
Social responsibility has tried instituted as the basis of educational strategy in medical schools worldwide, since, as forming potential health professionals are key in developing a health workforce aware of their reality actors. However, there are powers that ignore the importance of forming agents that generate a real impact on their society and are only interested in their educational or business needs (1).